Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 10- survey of adult behaviour of Culex nigripalpus and other species of Culex (Culex) in South-Eastern Brazil - Forattini, Oswaldo Paulo; Kakitani, Iná; Massad, Eduardo; Marucci, Daniel (Revista de Saúde Pública, 1995)
A survey of adult behaviour of Culex (Culex) species was carried out from August 1992 through December 1993 in a human modified (anthropic) environment in the Ribeira Valley, S.Paulo State, Brazil. Culex nigripalpus dominated the catches at several sites and it's tendency to increase in the anthropic environment became quite clear. Nevertheless no high level of synanthropy was demonstrated. So it seems that the mosquito may have a restricted role in natural arbovirus cycles. Nonetheless, Cx. nigripalpus must be considered a potential vector of arboviruses, especially St. Louis encephalitis virus outside dwellings.